Biopolitics in Roberto Bolaño’s 2666, “The Part About the Crimes” - Camelia Raghinaru (Altre Modernità, 2016)
Starting from Agamben’s theories of state of exception, and sovereignty and subalternity, this article looks at Roberto Bolaño’s 2004 novel, 2666, as a critique of neoliberal capitalism, where the law is predicated on violence and exploitation of surplus humanity—in this case, the poor female maquiladora workers at the U.S./Mexico border. Narco-trafficking and misogyny are symptomatic of a juridical and economic order that revolves around exploitation as central to the workings of transnational capitalism. As the boundary between legality and illegality breaks down, an aporetic state of exception forms, in which the transnational corporation acts as sovereign power by introducing a space of exception in the law. This force of law without law obscures the politicization of bare life, while maintaining traditional means of exploitation. The maquiladora workers emerge as docile bodies imprinted by the biopolitical power of sovereign financial capital. Powerless victims of overwork, displacement, destitution, and ultimately rape and slaughter, they objectify the violence of low wage labour in the global exchange of power and capital.